A Novel Overall Survival Prediction Signature Based on Comprehensive Research in Prostate Cancer Bone Metastases - Hu, Konghe; Hu, Xinyue; Duan, Yang; Li, Wenqiang; Qian, Jing; Chen, Junjie (Frontiers in Medicine, 2022)
Background: Prostate adenocarcinoma (PRAD)-related bone metastases are a leading source of morbidity and mortality; however, good diagnostic biomarkers are not known yet. The aim of this study was to identify biomarkers and prognostic indicators for the diagnosis and treatment of PRAD-associated bone metastases. Methods: We performed a comprehensive analysis of the expression differences, biological functions, and interactions of genes associated with PRAD bone metastasis. Annotation, visualization, and integrated discovery were accomplished through the use of gene ontology enrichment and gene set enrichment analysis. The protein-protein interaction network was constructed using the STRING database, and the diagnostic value of prognostic genes was validated using receiver-operating-characteristic and Kaplan-Meier curves. Results: Six genes (DDX47, PRL17, AS3MT, KLRK1, ISLR, and S100A8) associated with PRAD bone metastases were identified; these had prognostic value as well. Among them, enrichment was observed for the biological processes extracellular matrix tissue, extracellular structural tissue, steroid hormone response, and cell oxidative detoxification. KEGG analysis revealed enrichment in interactions with extra cellular matrix receptors, diseases including Parkinson's disease and dilated cardiomyopathy, and estrogen signaling pathways. The area under the curve values of 0.8938, 0.9885 and 0.979, obtained from time-dependent receiver-operating-characteristic curve analysis for 1-year, 3-year, and 5-year overall survival confirmed the good performance of the model under consideration. S100A8 expression was not detected in the normal prostate tissue but was detected in PRAD. Conclusions: By combining the data from The Cancer Genome Atlas(TCGA) and PRAD SU2C 2019, we identified ISLR as a potential biomarker for PRAD bone metastasis. Moreover, the genes identified to have prognostic value may act as therapeutic targets for PRAD bone metastasis.